Luteolin ameliorates rat model of metabolic syndrome-induced cardiac injury by apoptosis suppression and autophagy promotion via NR4A2/p53 regulation - Xiyan Dai; Bo Liang; Yaolin Sun (BMC Complementary Medicine and Therapies)
Abstract Background Reduced cardiac autophagy, inflammation, and apoptosis contribute to cardiovascular complications caused by metabolic syndrome (MetS). It is documented that the nuclear receptor 4A2 (NR4A2) could modulate autophagy and apoptosis in cardiac complications. The aim of this investigation was to assess the therapeutic potential of luteolin, with documented beneficial properties, against MetS-associated cardiac injury. Methods Forty male albino Wistar rats were divided into 5 groups randomly as controls, MetS, and MetS animals treated with luteolin (25, 50, 100 mg/kg ip). The animal’s weight, blood pressure, lipid profile, tolerance to glucose and insulin, and cardiac histopathology were evaluated. Moreover, troponin T, creatine kinase-myocardial band (CK-MB), inflammatory profile (IL-6, IL-1β, TNF-α), transforming growth factor-β1 (TGF-β1), oxidative stress, and matrix metalloproteinase-9 (MMP-9) were analyzed to determine the cardiac state. Cardiac NR4A2 and p53, as well as apoptotic (B-cell leukemia/lymphoma 2 [BCL-2], Caspase [CASP]-3, and CASP-9) and autophagic mediators (Sequestosome-1/p62, Microtubule-associated protein 1 A/1B-light chain 3 [LC3], and Beclin-1) were measured by RT-qPCR and ELISA. Results Luteolin remarkably restored MetS-induced biochemical derangements and related cardiac injury via the suppression of apoptosis, inflammation, and stress but promotion of autophagy (p-value < 0.001). Conclusion Current findings revealed the promising therapeutical properties of luteolin against MetS-associated cardiovascular risks.